Geopolitics of offshore oil exploration in the Caribbean Sea: border area between Colombia and Nicaragua - Pulido-Gómez, Ginneth (2018)
The border between Colombia and Nicaragua appears as a dynamic scenario characterized by a tension between the two countries due to their delimitation, comprising the archipelago of San Andrés, Providencia and Santa Catalina and the adjacent area in the western Caribbean Sea. To resolve this controversy, in 2012 the International Court of Justice determined that Colombia exercised sovereignty over the Archipelago and delimited new boundaries at sea, which modified the areas of usufruct of both countries. This region is important to the global geopolitical panorama for two main reasons. First, its proximity to the Panama Canal and to Nicaragua’s future Canal, strategic routes of world trade. And second, the interest shown by two countries in opening up oil exploration concessions at sea, within the framework of the current crisis regarding crude oil production, which translates into lower oil reserves, price fluctuations, and local and global socio-environmental impacts generated by all stages of the use of this resource. The purpose of this article is to discuss the validity of oil exploration and its growing interest in offshore areas, as well as the analysis of the resulting global relationships.